PROBLEMATIKA PENGATURAN PENDAFTARAN TANAH ADAT DI BALI - Wiguna, Made Oka Cahyadi (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2019)
Efforts to realize land registration of customary land in Bali are manifested in the provisions of Article 58 paragraph (1) of the Provincial Regulation of Bali No. 4 of 2019 concerning Customary Villages in Bali. The problem is that there is no juridical basis for the substance of the registration of land belonging to the Desa Adat, based on a hierarchy of laws. Then, there are various synchronization of regulations related to customary land registration objects in Bali. Its formation should have a strong juridical foundation. So that the legal building of the regulation becomes sturdy, in order to achieve the desired goals. Therefore, it is fitting to have a legal basis derived from higher legal norms in accordance with the hierarchy of laws and regulations. Various legal products governing the object of registration of customary land in Bali should need to be synchronized. The intention is to avoid overlapping arrangements over customary land registration objects in Bali. So that it can provide a guarantee of substantive legal certainty.